Seeing Red: A Grounded Theory Study of Women's Anger after Childbirth. (October 2022) - Ou, Christine H. K.; Hall, Wendy A.; Rodney, Paddy; Stremler, Robyn
Persistent intense anger is indicative of postpartum distress, yet maternal anger has been little explored after childbirth. Using grounded theory, we explained how and why mothers develop intense anger after childbirth and the actions they take to manage their anger. Twenty mothers of healthy singleton infants described their experiences of anger during the first two postpartum years. Mothers indicated they became angry when they had violated expectations, compromised needs, and felt on edge (e.g., exhausted, stressed, and resentful), particularly around infants' sleep. Mothers described suppressing and/or expressing anger with outcomes such as conflict and recruiting support. Receiving support from partners, family, and others helped mothers manage their anger, with more positive outcomes. Women should be screened for intense anger, maternal-infant sleep problems, and adequacy of social supports after childbirth. Maternal anger can be reduced by changing expectations and helping mothers meet their needs through social and structural supports.